Why a Hedonist should choose death? The Cyrenics and Socrates’ attitude towards the indictment - Mársico, Claudia (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
The phenomenon of the Socratic dialogue describes how many members of the circle attribute their own ideas to Socrates. This procedure provokes profiles distant from Plato or Xenophon’s variants. In this case, we are interested in the Hedonist Socrates built by Aristippus of Cyrene and his followers. We examine the Cyrenaic obstacles to justify Socrates’ strategy during the trial that was understood at the moment as a choice for death, which results incompatible with hedonistic principles. With this purpose, we will analyse the information from Papyrus Köln 205 that presents a Hedonist Socrates trying to explain his behaviour, and then we will study the elements in the Cyrenaic thought that make it compatible with Aristippus’ ideas. Thus, we will be able to elucidate relevant points of the link between pleasure, happiness and death in the Cyrenaic philosophy.